Polymorphism and protein expression of MUTYH gene for risk of rheumatoid arthritis. Issue 1 (December 2017) - Chen, Shih-Yin; Chen, Hsin-Han; Huang, Yu-Chuen; Liu, Shih-Ping; Lin, Ying-Ju; Lo, Sui-Foon; Chang, Yuan-Yen; Lin, Hui-Wen; Huang, Chung-Ming; Tsai, Fuu-Jen
Abstract Background We have previously described the association between rheumatoid arthritis (RA) prevalence and the two mutY Homolog (E. coli) (MUTYH) SNPs (rs3219463 and rs3219476) among the Taiwanese population. This present study will aim to elucidate whether the SNPs can alter the expression of EGFR in the progression of RA. Methods The cohort study included 368 Taiwan's Han Chinese RA patients and 364 healthy controls. Blood samples collected from the participants were analyzed to determine their serum MUTYH levels and to identify rs3219463 SNP of MUTYH from their genomic DNA. Results Our data resulted in a statistically significant difference in genotype frequency distributions at rs3219463 for RA patients and controls (p < 0.0002). Also, the patients with G carrier at rs3219463 were less likely to suffer from painful joints (p < 0.006) and DAS28 scores (p < 0.003). Furthermore, the increase in serum level of MUTYH was also observed in RA patients (p < 0.005). Conclusions Our study showed that RA is associated with rs3219463 SNP in EGFR gene and an increased serum level of the MUTYH protein. These findings suggest MUTYH is worthy of further investigation as a therapeutic target for RA.